2001
DOI: 10.2307/3323052
|View full text |Cite
|
Sign up to set email alerts
|

Forty Years of Social Mobility in France: Change in Social Fluidity in the Light of Recent Models

Abstract: The aim of this paper is to examine whether a long-term trend can be identified in the mobility regime of French society from the middle of the century. It begins with a review of the international literature on temporal trends in social fluidity within modern societies. Analysing recent French research which has concluded that inequality of opportunity has remained unchanged in France during the last two decades, the paper argues that such a conclusion can only have resulted from the use of insufficiently pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 25 publications
2
14
0
2
Order By: Relevance
“…It was shifted to a conceptual contribution so we will explain the meaning of MMI in the next section. Here we just note that the American case does not fit MMI (Hout, Raftery, and Bell 1993;Lucas 2001), and the Netherlands, Sweden, and France show evidence of declining class barriers even though the advantaged classes have not reached "saturation" (Ganzeboom and Nieuwbeerta 1996;Jonsson and Mills 1993;Vallet 2001) -negating a key element of MMI.…”
Section: ) Trends In Educational Stratification Favor Womenmentioning
confidence: 82%
“…It was shifted to a conceptual contribution so we will explain the meaning of MMI in the next section. Here we just note that the American case does not fit MMI (Hout, Raftery, and Bell 1993;Lucas 2001), and the Netherlands, Sweden, and France show evidence of declining class barriers even though the advantaged classes have not reached "saturation" (Ganzeboom and Nieuwbeerta 1996;Jonsson and Mills 1993;Vallet 2001) -negating a key element of MMI.…”
Section: ) Trends In Educational Stratification Favor Womenmentioning
confidence: 82%
“…the intrinsic strength of the association between sons' (daughters') occupation and fathers' occupation (Erikson & Goldthorpe, 1992). More recent studies concluded that the statistical association between social origin and destination has declined steadily since the end of World War II in France, though (Vallet, 2001). In that domain, the main characteristic of France, compared with many similar countries, is that school expansion has been relatively belated, with a dramatic increase in the number of secondary school graduates between 1985 and 1995, which has had a rather small and unclear impact on the reduction of inequalities in educational opportunities (Duru-Bellat & Kieffer, 2000;Duru-Bellat, 2008).…”
Section: Introductionmentioning
confidence: 93%
“…There are also cohort analyses in single countries assessing the effect of industrialization, educational expansion, market liberalization, and rising inequalities on mobility (Ishida 2001;Vallet 2001;Goldthorpe and Mills 2008). When combined, the two approaches have led to investigating the hypothesis of a secular convergence towards more fluidity driven by industrialization and post-industrialism.…”
Section: Application: Rationale For Case Selectionmentioning
confidence: 99%